Role of single nucleotide polymorphisms in pharmacogenomics and their association with human diseases. (3rd July 2015) - Chaudhary, Renu; Singh, Bharat; Kumar, Manish; Gakhar, Surendra K.; Saini, Adesh K.; Parmar, Virinder S.; Chhillar, Anil K.
Abstract: Global statistical data shed light on an alarming trend that every year thousands of people die due to adverse drug reactions as each individual responds in a different way to the same drug. Pharmacogenomics has come up as a promising field in drug development and clinical medication in the past few decades. It has emerged as a ray of hope in preventing patients from developing potentially fatal complications due to adverse drug reactions. Pharmacogenomics also minimizes the exposure to drugs that are less/non-effective and sometimes even found toxic for patients. It is well reported that drugs elicit different responses in different individuals due to variations in the nucleotide sequences of genes encoding for biologically important molecules (drug-metabolizing enzymes, drug targets and drug transporters). Single nucleotide polymorphisms (SNPs), the most common type of polymorphism found in the human genome is believed to be the main reason behind 90% of all types of genetic variations among the individuals. Therefore, pharmacogenomics may be helpful in answering the question as to how inherited differences in a single gene have a profound effect on the mobilization and biological action of a drug. In the present review, we have discussed clinically relevant examples of SNP in associated diseases that can be utilized as markers for "better management of complex diseases" and attempted to correlate the drug response with genetic variations. Attention is also given towards the therapeutic consequences of inherited differences at the chromosomal level and how associated drug disposition and/or drug targets differ in various diseases as well as among the individuals.